2020
DOI: 10.1016/j.neurobiolaging.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Adult brain aging investigated using BMC-mcDESPOT–based myelin water fraction imaging

Abstract: The relationship between regional brain myelination and aging has been the subject of intense study, with magnetic resonance imaging (MRI) perhaps the most effective modality for elucidating this. However, most of these studies have used nonspecific methods to probe myelin content, including diffusion tensor imaging, magnetization transfer ratio, and relaxation times. In the current study, we used the BMC-mcDESPOT analysis, a direct and specific method for imaging of myelin water fraction (MWF), a surrogate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 61 publications
15
31
2
Order By: Relevance
“…Noteworthy, some studies reported that in some brain regions (with emphasis on anterior brain areas), non-linear progressions of myelin proxies with age may be in closer agreements with histopathological findings of a preservation of myelin content during the first four decades of life, followed by a notable decrease of myelination in higher life decades, compared to linear trends (Peters, 2002;Lebel et al, 2012;Callaghan et al, 2014;Arshad et al, 2016). For instance, already in Flynn et al (2003) reported of protracted myelination in healthy individuals during the first decades of life, which reflects the statistical trends that have been reported in recent MWI studies (Arshad et al, 2016;Bouhrara et al, 2019). More extensive (longitudinal) imaging studies including higher subject numbers would be desirable to further validate these claims in terms of MWF estimates throughout different brain regions.…”
Section: Measures Of Dmri [Namely Neurite Orientation Dispersion and supporting
confidence: 86%
See 1 more Smart Citation
“…Noteworthy, some studies reported that in some brain regions (with emphasis on anterior brain areas), non-linear progressions of myelin proxies with age may be in closer agreements with histopathological findings of a preservation of myelin content during the first four decades of life, followed by a notable decrease of myelination in higher life decades, compared to linear trends (Peters, 2002;Lebel et al, 2012;Callaghan et al, 2014;Arshad et al, 2016). For instance, already in Flynn et al (2003) reported of protracted myelination in healthy individuals during the first decades of life, which reflects the statistical trends that have been reported in recent MWI studies (Arshad et al, 2016;Bouhrara et al, 2019). More extensive (longitudinal) imaging studies including higher subject numbers would be desirable to further validate these claims in terms of MWF estimates throughout different brain regions.…”
Section: Measures Of Dmri [Namely Neurite Orientation Dispersion and supporting
confidence: 86%
“…Accordingly, biomarkers sensitive for these specific developmental patterns of age-related myelin changes are of great interest for researchers studying aging. While many related imaging studies predominantly reported of linear declines of diffusion-based metrics (Bennett et al, 2010;Lebel et al, 2012;Billiet et al, 2015;Rathee et al, 2016), only very few studies found a correlation of MWF estimates with age (Billiet et al, 2015;Arshad et al, 2016;Faizy et al, 2018;Bouhrara et al, 2019). Histopathologically, normal brain-aging is marked by WM degeneration, including myelin pallor (Kemper, 1994), loss of myelinated nerve fibers (Bartzokis, 2004;Bartzokis et al, 2004) and malformation of myelin sheaths (Peters, 2002;Gunning-Dixon et al, 2009).…”
Section: Age-related Decreases Of Regional Mwfs May Reflect Myelin Comentioning
confidence: 99%
“…Compared to the BMC-mcDESPOT results of Bouhrara et al, our MWF in WM ROIs shows much more variation between individual subject values 28 . This could reflect the increased myelin-specificity of our 3D multi-echo T 2 relaxation MWI method, which is less sensitive to magnetisation transfer or other effects that could explain the unusually high, homogeneous MWF provided by mcDESPOT and its derivative techniques 28 . Our results also show increased variation in the trajectory of MWF with age between regions, which may better reflect the heterochronous brain development trajectories expected from literature 33 .…”
Section: Discussioncontrasting
confidence: 69%
“…The myelin-age relationship has also been studied using an alternative approach to MWI known as multicomponent-driven equilibrium single-component observation of T 1 and T 2 with Bayesian Monte Carlo analysis (BMC-mcDESPOT) 28 , which uses a more efficient steady state acquisition to provide a surrogate measure for the MWF 29 . Using a large sample and wide age range, Bouhrara et al (n = 106, range 22–94 years) found a quadratic association between myelin values and age 28 , similar to that found by Arshad et al and Papadaki et al 14 , 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation